Five are together again - Blyton, Enid (Hodder Children's London, 2011)
"Camping again! This time the fFve have pitched their tents near the house of a world-famous scientist. But then top secret papers go missing from the scientist's house. Can the Five find the thief and return the papers in time?--p. [4] of cover